Scientific creativity in secondary students and its relationship with STEM-related attitudes, engagement and work intentions - Pont-Niclòs, Isabel; Martín-Ezpeleta, Antonio; Echegoyen-Sanz, Yolanda (Frontiers in Education, 2024)
The role of creativity in education is pivotal, since it is regarded as an essential skill enabling students to cope with future challenges, not only at their professional, but also at their daily life. Consequently, the assessment and improvement of creativity skills among secondary school students has been tackled both at international (OECD reports and the recent inclusion of creativity in the 2022 PISA tests) and national spheres (such as the LOMLOE law at Spain, in which this study is framed). In this context, this longitudinal quasi-experimental study explores the scientific creativity performance of Spanish secondary students (N = 780) and its relationship with their attitudes and engagement towards science, and work intentions in STEM-related careers. Results show a noteworthy deficiency in scientific creativity, in terms of problem-finding abilities, alongside with moderately accurate and positive perceptions about how science works and its individual and collective implications. In addition, limited engagement in science-related activities and a low rate of expectations in pursuing STEM-related careers have also been detected. Gender differences were found in scientific creativity, as well as perceptions and career expectations related to science. No differences were found in the scientific creativity across the levels of compulsory secondary school, but an improvement in perceptions about science was observed as the students progressed in the educational system. Nevertheless, a decrease in the rate of engagement and willingness to embracing a STEM-related pathway has also been detected in higher levels. Positive correlations between engagement and career expectations related to science were also found. The importance of nurturing scientific creativity is discussed in terms of enriching learning experiences and the design of interventions and specific policies. Finally, the impact of implementing creativity-focused educational strategies is highlighted in order to promote interest in pursuing STEM careers beyond the obligatory boundaries of education.